Bilingual Europe : Latin and Vernacular Cultures, Examples of Bilingualism and Multilingualism c. 1300-1800 - Bloemendal, Jan, 1961- (Brill's studies in intellectual history, 2015)
Bilingual Europe presents to the reader a Europe that for a long time was 'multilingual': besides the vernacular languages Latin played an important role. Even 'nationalistic' treatises could be written in Latin. Until deep into the 18th century scientific works were written in it. It is still an official language of the Roman Catholic Church. But why did authors choose for Latin or for their native tongue. In the case of bilingual authors, what made them choose either language, and what implications did that have? What interactions existed between the two? Contributors include Jan Bloemendal, Wiep van Bunge, H. Floris Cohen, Arjan C. van Dixhoorn, Guillaume van Gemert, Joep T. Leerssen, Ingrid Rowland, Arie Schippers, Eva Del Soldato, Demmy Verbeke, Françoise Waquet, and Ari H. Wesseling. --